PENINGKATAN HASIL BELAJAR SISWA KELAS VIII DENGAN MODEL KANCING GEMERINCING - Zebua, Talenta Putri Sari; Lase, Asali; Laoli, Eka Septianti; Lahagu, Arianto (Yayasan Amanah Nur Aman, 2025)
Conventional learning methods often create obstacles for students in understanding various subjects. At UPTD SMP Negeri 1 Idanoi, this issue frequently occurs, especially in Grade VIII, where many students tend to feel sleepy and lose focus due to their inability to grasp the subject matter. Based on this problem, the aim of this study is to determine student learning outcomes through the implementation of the Kancing Gemerincing learning model. The research method used is classroom action research, with the research subjects being 32 students from class VIII-A. The results of the study showed that in Cycle I, the average student observation score reached 45.11%, while in Cycle II, it increased significantly to 87.49%. Meanwhile, the average score for students’ learning evaluations in Cycle I was 74.25%, which further increased to 80.43% in Cycle II. This improvement demonstrates the success of the Kancing Gemerincing Learning Model in enhancing student learning outcomes in the Integrated Social Studies subject for Grade VIII at UPTD SMP Negeri 1 Gunungsitoli Idanoi.